The Feeling of Tolerance in the World View of Educated Youth - Kadirova F. Q. (Web of Journals Publishing, 2023)
The spiritual world of a person determines his tolerance, attitude towards another person with appreciation and respect for his rights. All these qualities should be inculcated from a younger age, since at this age good acquired knowledge remains forever. Tolerance is an important factor for the stable development of the state and society.
Keywords: spirituality, people, personality, upbringing, tolerance, freedom.